2016
DOI: 10.1080/1331677x.2016.1193945
|View full text |Cite
|
Sign up to set email alerts
|

Public accounting history in post-communist Romania

Abstract: Having a longitudinal approach of the Romanian public accounting system's evolution, this historical study proposes the development of a framework in order to assess in a descriptive manner the change of public accounting and its implications for Romania, a European emerging country. The evolution from cash accounting to accrual accounting took place during three time periods within the timeframe 1991-2015. For each of these time periods we investigated influential factors such as period, place, people, practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Chan (2016) found that the Chinese government's decision to adopt accrual accounting can be attributed to a desire to counteract local government debt and reduce fiscal risk. Nistor and Deaconu (2016) associated the Romanian adoption of accrual accounting with international managerial public reform and internal factors.…”
Section: Results Of the Systematic Literature Reviewmentioning
confidence: 99%
“…Chan (2016) found that the Chinese government's decision to adopt accrual accounting can be attributed to a desire to counteract local government debt and reduce fiscal risk. Nistor and Deaconu (2016) associated the Romanian adoption of accrual accounting with international managerial public reform and internal factors.…”
Section: Results Of the Systematic Literature Reviewmentioning
confidence: 99%
“…Previous research discussed more on the benefits and usefulness of applying the accrual basis (Monteiro & Gomes, 2013;PwC, 2013;Chan, 2016), obstacles and challenges in the application (Harun & Robinson, 2010), the factors influencing adoption (Adhikari & Mellemvik, 2011;Harun et al, 2012), and provision of information for better decision making (Hyndman & Connolly, 2011). Moreover, previous studies highlighted more on explaining increasing efficiency, transparency, and accountability (Chan, 2016;Hodges & Mellett, 2003;Monteiro & Gomes, 2013;Nistor & Deaconu, 2016). Likewise, Tickell (2010) in Fiji, Tanjeh (2016) in Cameroon, and Azmi and Mohamed (2014) in Malaysia specifically tended to focus on readiness in implementing the accrual system.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this lack of accounting harmonization and the presence of urgent financial problems, the European Commission (EC) implemented a project to harmonize public sector accounting in 2013 (EC, 2013; Manes-Rossi et al., 2016a). The introduction of the European Public Sector Accounting Standards (EPSAS) should pave the way to European accounting harmonization (Mann et al., 2019; Nistor and Deaconu, 2016). Although the International Public Sector Accounting Standards Board (IPSASB) has been pushing forward the development of the International Public Sector Accounting Standards (IPSAS) (Sellami and Gafsi, 2019), the usefulness of IPSAS in relation to enhancing public sector accounting is highly controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Government and accounting systems have been changing significantly during recent decades (Manes-Rossi et al, 2016b). In line with the New Public Management (NPM) paradigm and economic rationalities (Nistor and Deaconu, 2016), financial information systems have been aligned towards an enhanced level of accountability and transparency (Brusca et al, 2018;Christiaens et al, 2015). These accounting innovation efforts are associated with the implementation of accrual accounting at the expense of cash accounting in the public sector (Deaconu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%